Interdisciplinary Synthetic Classifier in the Subject Area “Innovations and Innovation Management” - Chuikova, N. A. (Scientific and technical information processing, 2025)
The article examined the development of a model of information retrieval language in the form of an interdisciplinary synthetic classifier as a set of interlinked notations and polyhierarchical links of classification branches in the subject area “Innovations and Innovation Management.” The general collection of keywords and phrases, as well as subject headings of the VINITI Classifier, linked to the studied information array was presented. The links of the headings of this collection with the State Classifier of Scientific and Technical Information and the Universal Decimal Classification were taken into account. A statistical core (18 units) of the collection of subject headings was identified. Analysis was made of the keywords and subject entries under the most commonly used headings: 061.54.45 “Innovation Activity” and 061.54.31 “Scientific and Technological Progress. New Technologies. Innovations. Research and Development.” The cores of many subject entries were constructed, and an expert-analytical assessment was carried out, supplementing the obtained results.